Strategies to Prevent and Manage Thrombotic Complications of Acute Lymphoblastic Leukemia in Children and Young People Vary Between Centers in the United Kingdom. Issue 3 (April 2016) - Biss, Tina T.; Payne, Jeanette H.; Hough, Rachael E.; Grainger, John D.; Macartney, Christine; Sibson, Keith R.; Chalmers, Elizabeth A.
Abstract : There is a lack of evidence-based guidance for the prevention and management of thrombosis in children and young people treated for acute lymphoblastic leukemia. To determine current UK practice, a survey was sent to 28 centers participating in the Medical Research Council UKALL 2011 trial. Marked variation in practice was noted. In total, 43% of centers defer central venous access device insertion until end of induction for treatment of low-risk disease. Central venous access devices are removed at the end of intensive blocks in 38% and end of treatment in 42%. Duration of anticoagulation for line-associated thrombosis is 6 weeks in 43% and 3 months in 33% and for cerebral sinovenous thrombosis is 3 months in 71% and 6 months in 24%. Platelet transfusion to maintain platelet count >50×10 9 /L, in preference to interrupting therapeutic anticoagulation, is used by 50% for line-associated thrombosis and 73% for cerebral sinovenous thrombosis. Conformity of practice was seen in some areas. In total, 70% treat thrombosis with twice-daily low–molecular weight heparin and 86% monitor antifactor Xa activity levels. In total, 91% reexpose individuals to asparaginase following a thrombotic event. Given this variation in practice, in the absence of high-quality evidence, consensus guidelines may be helpful.